Escape from rich‐to‐lean transitions: Stimulus change and timeout. Issue 1 (11th January 2017) - Retzlaff, Billie J.; Parthum, Elizabeth T. P.; Pitts, Raymond C.; Hughes, Christine E.
Abstract : Extended pausing during discriminable transitions from rich‐to‐lean conditions can be viewed as escape (i.e., rich‐to‐lean transitions function aversively). In the current experiments, pigeons' key pecking was maintained by a multiple fixed‐ratio fixed‐ratio schedule of rich or lean reinforcers. Pigeons then were provided with another, explicit, mechanism of escape by changing the stimulus from the transition‐specific stimulus used in the multiple schedule to a mixed‐schedule stimulus (Experiment 1) or by producing a period of timeout in which the stimulus was turned off and the schedule was suspended (Experiment 2). Overall, escape was under joint control of past and upcoming reinforcer magnitudes, such that responses on the escape key were most likely during rich‐to‐lean transitions, and second‐most likely during lean‐to‐lean transitions. Even though pigeons pecked the escape key, they paused before doing so, and the latency to begin the fixed ratio (i.e., the pause) remained extended during rich‐to‐lean transitions. These findings suggest that although the stimulus associated with rich‐to‐lean transitions functioned aversively, pausing is more than simply escape responding from the stimulus.